Phytotoxicity of sewage sludge passivated by modified potassium feldspar and its effect on ryegrass growth. Issue 1 (31st December 2023) - Xie, Tianyu; Li, Fengchun; Cao, Heng; Ge, Chenglong; Zhao, Wenhao; Zhao, Ying; Zhang, Xuan
ABSTRACT: Effective passivation of heavy metals in sludge is the key to achieve its land use. Potassium feldspar was modified to obtain G×K900, with a lower crystallinity, a higher specific surface area and cationic exchange capacity. G×K900 was chosen to passivate heavy metals in the sludge, and the best passivation conditions were 30% addition and a 10-day passivation period. The passivated sludge extract had no adverse effects on ryegrass germination and promoted radicle growth. The pot experiment revealed that adding 10% passivated sludge encouraged ryegrass growth while having no appreciable impact on the contents of Cu, Cr, Zn and Pb in the roots and above-ground parts compared to control treatment. The transfer factors of the four metals were all less than 1. Passivated sludge was used as a growing medium for landscaping plants, which provided a theoretical foundation for sludge land use and a resource outlet for potassium feldspar minerals.